Streamshield: an anti-piracy movie streaming android application with screen recording detection and integrated media content protection using advance encryption standard (AES) algorithm - Besario, Voltaire M.; Manlutac, Bernard D.; Quiazon, Mark Cristian D. 4 0 16; 5 (2024)
u
Undergraduate Thesis: (Bachelor of Science in Information Technology) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2